"This Mystical Blessing"1: The Patristic Roots of John Calvin's Eucharistic Theology. Issue 3 (August 2021) - Butler, Geoffrey
Though committed to the final authority of Scripture in all matters, John Calvin's Institutes and biblical commentaries show him to be a remarkable student of patristics. His doctrine of the Lord's Supper was no exception, as Calvin calls upon the likes of Augustine, Chrysostom, Tertullian and others to support his position. This article, therefore, contends that Calvin's engagement with the Fathers – though imperfect – demonstrates that his view, in essence, may be clearly traced to the patristic period. It also suggests that his reverence for tradition, which he considered consistent with his commitment to sola scriptura, makes Calvin a prime example for contemporary evangelicals as they reflect on their own doctrine of the Supper. Not only would paying close attention to the Fathers enrich their own understanding, but given that such figures are esteemed by the wider church, it may well contribute to a more robust ecumenical conversation around the sacraments.